CEO Duality and Environmental Efficiency : Empirical Case Study on Chinese Publicly Listed Companies between 2015-2024 - El Taher, Mariam Ahmed (AUC Knowledge Fountain, 2026)
Abstract The paper investigates the potential effects of CEO duality—where the CEO also chairs the board—on environmental efficiency in Chinese listed companies between 2015 and 2024. Energy intensity, or total energy use per unit of revenue, serves as a stand-in for environmental efficiency. In the full sample, CEO duality is consistently linked to higher energy intensity (≈19–27 units; p< 0.01) using firm, year, and (in the pooled models) sector fixed effects with firm-clustered standard errors, suggesting lower environmental efficiency under unified leadership. In line with creditor discipline, market capitalization is typically negative and substantial, headcount is positive, and leverage (Net Debt/EBITDA) is negative. Moderation tests reveal that leverage significantly reduces the duality–inefficiency link (Duality×Leverage ≈ −0.49; p< 0.05), while interactions with board conflicts, working capital, gender diversity, and disclosure/independence are statistically insignificant. The study uses an instrumental-variable estimation to account for potential endogeneity, where CEO duality may itself be influenced by unobserved firm characteristics or past performance. Diagnostic tests (Anderson LM, Cragg–Donald F, and Sargan) confirm that the instrument, which is based on the sector's historical propensity to adopt dual leadership, satisfies both relevance and exclusion conditions. This demonstrates that the positive relationship between CEO duality and energy intensity reflects a structural governance effect rather than just correlation, supporting the causal interpretation of the findings. Heterogeneity is revealed by sectoral splits. Duality is still firmly positive in sensitive industries (energy, technology, industrials, and basic materials), and leverage significantly increases efficiency. The duality effect is beneficial in simpler specifications in cyclical industries (consumer cyclicals, financials, and real estate), but it diminishes when governance/conflict controls are implemented. Small samples restrict inference, and estimates are imprecise in defensive industries (utilities, healthcare, and consumer non-cyclicals). Duality is highly positive for pre-1999 incumbents, according to age-cohort tests; for post-1999 firms, duality becomes significant mainly in leverage-rich specifications, emphasizing the importance of capital structure. Multicollinearity issues are not indicated by variance-inflation factors (mean ≈1.7). The evidence generally favors a contingency view of CEO duality, which shows that while it generally increases energy intensity, capital structure, more so than board demographics, consistently reduces this effect. The results encourage governance practices that acknowledge funding limitations as an external discipline, strengthen oversight in dual-led companies, and link executive compensation to measurable resource efficiency.